Spatial contagion structures urban vegetation from parcel to landscape. Issue 1 (9th October 2021) - Locke, Dexter Henry; Ossola, Alessandro; Minor, Emily; Lin, Brenda B.
Abstract: Residential yards are a significant component of urban socio‐ecological systems; residential land covers 11% of the United States and is often the dominant land use within urban areas. Residential yards also play an important role in the sustainability of urban socio‐ecological systems, affecting biogeochemical cycles, water and the climate via individual‐ and household‐level behaviours. Spatial contagion has been observed in yard vegetation in several cities, potentially due to social norms that compel neighbours to emulate or conform to specific aesthetic qualities or management regimes. Residents may feel obliged to mow their front yards or prune their trees, creating patterns of spatial autocorrelation in residential neighbourhoods. In this study, we examined the spatial autocorrelation of several yard vegetation characteristics in both front and backyards in Boston, MA, USA. Our study area included 1, 027 Census block groups (sub‐neighbourhood areas) and 175, 576 parcels with matched front‐backyard pairings ( n  = 351, 152 yards in total) across Boston's metropolitan area. We spatially defined 'neighbours' in five ways to better account for the potentially variable nature of how conformity or contagion manifests in empirical terms. We anticipated front yards to have stronger spatial autocorrelation due to the more publicly visible nature of these green spaces. We found positive and significant spatial autocorrelation in all measured vegetation variables, in both front and backyards. Unexpectedly, spatial autocorrelation tended to be higher in backyards for tree canopy variables but higher in front yards for turf grass cover. Among block groups, different socio‐economic variables, such as median household income, predicted spatial autocorrelation of vegetation characteristics. Our results were sensitive to how neighbours were spatially defined. Our results further underscore the importance of backyards as critical areas for sustaining an urban tree canopy, and show that spatial patterns vary across different social groups. The importance of 'neighbour' definition indicates opportunities to think carefully about the mechanisms driving spatial autocorrelation and the scales at which patterns develop. The identification of these mechanisms will have important implications for scales of policy and implementation for urban and suburban greening. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.